THE ELUCIDATION OF THE ETHICS OF CONVERSATION IN FAKHRUDDIN ALI SAFIY’S WORK “ODOB UL-AS’HAB” (TAMADDUN NURI JURNALI, 2025)
This article analyzes the life and work of Fakhruddin Ali Safiy based on reliable sources. It also provides an in-depth exploration of his scientific heritage, particularly his role in his time, the thematic directions of his works, and their relevance to contemporary science.